Characterization of mannitol-fermenting methicillin-resistant staphylococci isolated from pigs in Nigeria - Ugwu, Clifford C. (Braz J Microbiol, 2015)
This study was conducted to determine the species distribution, antimicrobial resistance pheno- and genotypes and virulence traits of mannitol-positive methicillin-resistant staphylococci (MRS) isolated from pigs in Nsukka agricultural zone, Nigeria. Twenty mannitol-positive methicillin-resistant coagulase-negative staphylococcal (MRCoNS) strains harboring the mecA gene were detected among the 64 Staphylococcus isolates from 291 pigs. A total of 4 species were identified among the MRCoNS isolates, namely, Staphylococcus sciuri (10 strains), Staphylococcus lentus (6 strains), Staphylococcus cohnii (3 strains) and Staphylococcus haemolyticus (one strain). All MRCoNS isolates were multidrug-resistant. In addition to β-lactams, the strains were resistant to fusidic acid (85%), tetracycline (75%), streptomycin (65%), ciprofloxacin (65%), and trimethoprim/sulphamethoxazole (60%). In addition to the mecA and blaZ genes, other antimicrobial resistance genes detected were tet(K), tet(M), tet(L), erm(B), erm(C), aacA-aphD, aphA3, str, dfrK, dfrG, cat (pC221), and cat (pC223). Thirteen isolates were found to be ciprofloxacin-resistant, and all harbored a Ser84Leu mutation within the QRDR of the GyrA protein, with 3 isolates showing 2 extra substitutions, Ser98Ile and Arg100Lys (one strain) and Glu88Asp and Asp96Thr (2 strains). A phylogenetic tree of the QRDR nucleotide sequences in the gyrA gene revealed a high nucleotide diversity, with several major clusters not associated with the bacterial species. Our study highlights the possibility of transfer of mecA and other antimicrobial resistance genes from MRCoNS to pathogenic bacteria, which is a serious public health and veterinary concern.